Biomonitoring polycyclic aromatic hydrocarbons by Salix matsudana leaves: A comparison with the relevant air content and evaluation of environmental parameter effects. (May 2018) - Zhao, Xiangai; He, Miao; Shang, Haibo; Yu, Hongling; Wang, Hao; Li, Huijie; Piao, Jingyi; Quinto, Maurizio; Li, Donghao
Abstract: Studies on seasonal distribution characteristics of polycyclic aromatic hydrocarbons (PAHs) in Salix matsudana leaves covering its annual life cycle were carried out in order to evaluate plant leaf response sensitivity to air pollution. Salix matsudana leaves were collected throughout different development phases of plant leaf inclusive of bud break to fallen leaves, covering from spring (May) to autumn (November). Simultaneously, particle and gas samples were collected using a high volume air sampler. Seven different PAHs were determined simultaneously in these samples. The temperature dependence of the partitioning of PAHs in air and plant leaves was investigated and the results were incorporated into a mathematical model. The measured plant/air partition coefficients have been found to be exponentially proportional to the reciprocal temperature, in agreement with theoretical expectations. Furthermore, in order to define the influence of different parameters on PAH adsorption on plant leaves, area and lipid leaf content were also measured. Results demonstrated that temperature plays a very important role in PAHs partitioning and that this value should be carefully considered during sampling, in order to obtain the best correlation between PAHs concentration in air and leaves. Highlights: PAHs were determined in Salix matsudana leaves covering its annual life cycle. PAHs were also determined in atmospheric particle and gas phase samples. It is found the measured plant/air partition coefficients have exponentially proportional to the reciprocal temperature. Temperature plays a very important role in PAHs partitioning in air and leaves.